Evaluation of intra-ovarian platelet-rich plasma administration on oocytes-dependent variables in patients with poor ovarian response: A retrospective study according to the POSEIDON criteria - Marzieh Farimani; Arash Nazari; Shahrzad Mohammadi; Roghayeh Anvari Aliabad (BMC, 2021)
Abstract Background Poor ovarian response (POR) is among the common findings in infertile women with no significant underlying condition. The aim of this study was to investigate the intra-ovarian potential of platelet-rich plasma (PRP) administration on oocytes-dependent variables in the POR women grouped according to the POSEIDON criteria. Methods This retrospective study was performed on POR women with no underlying condition who have undergone intra-ovarian PRP injection. As well as patients' age, the number of total and MI, MII, and GV oocytes were extracted from the files. The laboratory variables including anti-mullerian hormone (AMH), follicle-stimulating hormone (FSH), luteinizing hormone (LH), and estradiol were also gathered. In order to reduce any bias due to the possible differences in kits or devices, a single laboratory with the highest number of cases was selected and others were excluded from the study. Then, the included cases were grouped into four according to the POSEIDON criteria and analyzed for the mentioned variables by SPSS, version 25. The statistical significance level was set as P-value < 0.05. Results From 383 cases, a total number of 96 women were enrolled in this study. According to the POSEIDON criteria, group 4 (Age ≥ 35 years, AMH < 1.2 ng/mL) with the ratio of 56/96 (58.3%) had the highest prevalence among others. As the analyses showed, changes in the laboratory variables (LH, FSH, AMH, and estradiol) were not significant in almost all the groups following the intervention. Regarding the total oocytes number, PRP administration caused a significant increase in the total number in all the groups (all P < 0.05). Also, the number of MII oocytes was significantly increased following the treatment in all groups except for group 2 (Age ≥ 35 years, AMH ≥ 1.2 ng/mL; all P < 0.05). Of 96 cases, 14 (14.6%) got clinically pregnant following assisted reproductive techniques which this number were significantly differed among the groups (P = 0.002). Conclusion This study showed that PRP treatment was effective on total and MII oocyte numbers in the patients with POR, however, further studies are required.